2022
DOI: 10.1101/2022.01.17.476643
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conservation and divergence of myelin proteome and oligodendrocyte transcriptome profiles between humans and mice

Abstract: Human myelin disorders are commonly studied in mouse models. Since both clades evolutionarily diverged approximately 85 million years ago, it is critical to know to what extent the myelin protein composition has remained similar. Here we use quantitative proteomics to analyze myelin purified from human white matter and find that the relative abundance of the structural myelin proteins PLP, MBP, CNP and SEPTIN8 correlates well with that in C57Bl/6N-mice. Conversely, multiple other proteins were identified exclu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 73 publications
(148 reference statements)
0
7
0
Order By: Relevance
“…However, newly formed oligodendrocytes are absent from the human dataset and the SPARC -positive, RBFOX1 -negative human cluster Oligo_F is missing in the mouse datasets, even in the adult mouse spinal cord samples, suggesting it may be human-specific (2g,h). There are proteomic differences between human and murine CNS myelin including the human-specific expression of Peripheral Myelin Protein 2 ( PMP2 ) 41 , which is highly expressed in Oligo_F and therefore may contribute to this observed proteomic species differences. More intermediate cells between the state of OPCs and oligodendrocytes were found in the mouse data, particularly in the juvenile data (2g,h), consistent with our data suggesting that human adult normal CNS cells are not actively differentiating.…”
Section: Resultsmentioning
confidence: 99%
“…However, newly formed oligodendrocytes are absent from the human dataset and the SPARC -positive, RBFOX1 -negative human cluster Oligo_F is missing in the mouse datasets, even in the adult mouse spinal cord samples, suggesting it may be human-specific (2g,h). There are proteomic differences between human and murine CNS myelin including the human-specific expression of Peripheral Myelin Protein 2 ( PMP2 ) 41 , which is highly expressed in Oligo_F and therefore may contribute to this observed proteomic species differences. More intermediate cells between the state of OPCs and oligodendrocytes were found in the mouse data, particularly in the juvenile data (2g,h), consistent with our data suggesting that human adult normal CNS cells are not actively differentiating.…”
Section: Resultsmentioning
confidence: 99%
“…6b, Supplementary Table 5). 98% of the VAMP2/3-dependent hits had also been detected in acutely isolated oligodendrocytes from mouse brains and from purified myelin, validating the ability of primary culture to recapitulate in vivo oligodendrocytes 24,50,51 . Gene ontology analysis revealed a significant enrichment of proteins that localize to myelin sheaths, paranodes, cell-cell junctions, and vesicles (Fig.…”
Section: Oligodendrocyte Vamp2/3 Is Required For Delivery Of Myelin A...mentioning
confidence: 65%
“…Further, CMTM5 is expressed by oligodendrocytes of mice and humans (Figure 3C, F) (Jäkel et al, 2019;Zhou et al, 2020) and was also mass-spectrometrically identified in purified CNS myelin before (Jahn et al, 2020). Additionally, we identified CMTM5 in myelin derived from wildtype mice and non-diseased humans (Fig 3G) and found the abundance to be roughly equal between the two species (Gargareta et al, 2022). (Zhang et al, 2014).…”
Section: The Cmtm Protein Family and Its Relevance For Nervous System...mentioning
confidence: 70%
“…From all the members of the CMTM protein family only CMTM5 is expressed in myelinating oligodendrocytes to a considerable amount (Figure 3A, B). Further, the expression of CMTM5 is mostly specific for cells of the oligodendrocyte lineage in humans and mice (Figure 3C-F) and was identified in datasets analyzing myelin (Gargareta et al, 2022;Jahn et al, 2020) of both species. To date, CMTM5 has never been described as a CNS myelin protein and its function in oligodendrocytes has not been investigated until now.…”
Section: Identification Of Cmtm5 As a Cns Myelin Proteinmentioning
confidence: 94%
See 1 more Smart Citation